Characteristics of upper-body pull exercise power in Japanese female wrestlers - Kanno, M.; Shidochi, S.; Sakae, K.; Shima, N. (The Journal of Physical Fitness and Sports Medicine, 2016)
[Aims] This study aimed to compare the pull power, power endurance, and number of repetitions of female wrestlers with those of track-and-field sprinters to elucidate the physical strength characteristics required by female wrestlers. [Methods] Twenty female wrestlers (8 Olympic- and/or world-class and 12 national-class) and 14 female sprinters (including 3 championship students) performed upper-body pull. Subjects lie in a prone position on a bench and pull a barbell. Their power was measured by every-10 kg increased weight. To measure power endurance, the power to reach and number of maximum repetitions were measured using the load at their maximum power. All measurements were obtained using a power meter (GymAware). [Results] Subjects in the wrestler group demonstrated more power at 30, 40, and 50 kg than subjects in the sprinter group. Although both groups showed a significant reduction in power endurance after at least 30% of the number of maximum repetitions, the wrestler group showed a significantly higher number of maximum repetitions. The world-class wrestlers had abilities that exceeded those of the national-class wrestlers. [Conclusions] Female wrestlers were characterized by their ability to exert high upper-body pull power under heavy loads, and their ability to maintain a high level of power and to repeat motions. These abilities are related to their competitive performance. This study suggests that higher pull power endurance in the upper-body play a role in improving their competitive performance level.